Risk stratification to guide management in cardiogenic shock due to acute myocardial infarction. An illustrative case series and review of the literature - Rajkumar Rajendram (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
In patients who sustain an Acute Myocardial Infarction (AMI), Cardiogenic Shock (CS) is the most common cause of inpatient death. Despite significant advances in medical and surgical management, mortality rates approaching 80% have been described in some cohorts. However, the severity of CS and outcomes after AMI vary widely. Management requires a rapid, well-organised response and accurate risk stratification must guide complex decisions on ceilings of therapy in the acute setting. Whilst validated risk scores (e.g. the IABP-SHOCK II score and the CardShock score) are available, as highlighted in the present illustrative case series, their use must be guided by clinical judgement. in the setting of CS due to AMI, it is the author's opinion that, the IABP-SHOCK II score should be used for risk stratification after PCI. It may also be appropriate to use the IABP-SHOCK II score in conjunction with the operator's opinion on the likelihood of restoration of TIMI 3 flow if the coronary anatomy and targets for PCI are known. However, in patients with AMI who develop CS prior to angiography the author recommends use of the CardShock score for risk stratification rather than consider the pre-PCI IABP-SHOCK II score. However, more data are required to validate this approach.